A Philosophical Examination of Social Justice and Child Poverty - Schweiger, G.; Graf, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book is open access under a CCBY license. This book investigates child poverty from a philosophical perspective. It identifies the injustices of child poverty, relates them to the well-being of children, and discusses who has a moral responsibility to secure social justice for children. .
Keywords: Political science -- Philosophy; Social sciences -- Philosophy; Economic development; Ethics; Social structure; Equality; Human rights; Political Philosophy; Social Philosophy; Development Studies; Moral Philosophy and Applied Ethics; Social Structure; Human Rights